2023
DOI: 10.3390/ijerph20032292
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of China’s ETS on Corporate Green Governance Based on the Perspective of Corporate ESG Performance

Abstract: To achieve China’s “dual carbon” and common prosperity goals, corporate green governance is crucial. A key tool for promoting green growth is environmental legislation, particularly market-based regulation. With China’s carbon emission trading as a natural experiment, we adopt the DID method to quantitatively compare the gap between ESG performance of pilot and non-pilot carbon trading enterprises before and after policy implementation, thereby examining the impact, mechanism and optimization conditions of mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…The results in Table 3 show that the emission reduction effect of carbon trading policy is affected by the degree of regional marketization: the degree of marketization plays a positive moderating role in the relationship between the role of carbon trading policy on carbon emission reduction of enterprises, and all of them are significant at the 1% level. This result is consistent with the results of existing studies, that is, the emission reduction effect of carbon trading is more significant in regions with higher levels of marketization, indicating that market-oriented reforms can effectively enhance the effectiveness of the policy and achieve the goal of low-carbon development (Wang et al, 2023;Yao et al, 2023).…”
Section: Heterogeneity Analysissupporting
confidence: 91%
“…The results in Table 3 show that the emission reduction effect of carbon trading policy is affected by the degree of regional marketization: the degree of marketization plays a positive moderating role in the relationship between the role of carbon trading policy on carbon emission reduction of enterprises, and all of them are significant at the 1% level. This result is consistent with the results of existing studies, that is, the emission reduction effect of carbon trading is more significant in regions with higher levels of marketization, indicating that market-oriented reforms can effectively enhance the effectiveness of the policy and achieve the goal of low-carbon development (Wang et al, 2023;Yao et al, 2023).…”
Section: Heterogeneity Analysissupporting
confidence: 91%
“…This leads to high-quality companies finding it challenging to obtain substantial funding for innovative activities, while less efficient companies can continue to acquire funds for less efficient production models. In [11], the authors demonstrated that the ESG rating of listed companies can reflect a company's level of corporate governance and effectively indicate the quality of information disclosure. There exists a significant positive correlation between these two aspects.…”
Section: Esg Performance and Total Factor Productivitymentioning
confidence: 99%
“…There exists a significant positive correlation between these two aspects. Additionally, higher levels of corporate governance can effectively reduce situations where management sacrifices the company's long-term interests for personal gains due to agency problems and significantly curb the interests' encroachment by major shareholders [11][12][13]. By fully disclosing relevant information, companies enable investors to better understand their developmental status, facilitating the movement of capital in the capital market toward high-quality companies.…”
Section: Esg Performance and Total Factor Productivitymentioning
confidence: 99%
“…The adoption of an environmental protection tax in China has increased either the ESG orientation of firms either the ability of companies to invest in green patenting [22]. Environment Trade System-ETS has a positive impact either on ESG either on green patenting in China [23].…”
Section: Literature Reviewmentioning
confidence: 99%